Hubungan Pengetahuan dengan Keikutsertaan Ibu Hamil dalam Program Vaksinasi Covid-19 - Chintya Cristin Apta Saputri Paserang; Andi Nilawati Usman; Muh Nasrum Massi; Firdaus Hamid; Isharyah Sunarno; Muhammad Tamar (Malahayati Nursing Journal, 2023)
ABSTRACT Pregnant women are more susceptible to disease or infection, during the Covid-19 pandemic, it is very important for pregnant women to know the risks that can occur when the body is infected with the Covid-19 virus because pregnant women are more likely to have a low immune system. In addition, various studies have also stated that pregnant women who have had the Covid-19 vaccine can develop antibodies that are in the baby's umbilical cord blood. This suggests that the baby may receive the protective benefits of the vaccine, in addition to the benefits for pregnant women. The purpose of this study was to analyze the relationship between knowledge and the participation of pregnant women in the Covid-19 vaccination program at the Community Health Center in South Manokwari District, Manokwari Regency. This type of research is an analytical research with a cross-sectional study approach which aims to analyze the relationship between knowledge and participation of pregnant women in the Covid-19 vaccination program where the independent variables and dependent variables are measured at the same time. The researcher only made observations without intervening in the research subjects. The sample in this study were all pregnant women who visited the Health Center in South Manokwari District using a total sampling technique. This study uses human research subjects, namely as many as 108 respondents who will be given a questionnaire. Researchers asked the willingness of pregnant women to become research respondents. Explaining the purpose and benefits of the research, then signing an agreement to participate in the research after getting an explanation. Researchers gave questionnaires to respondents. Invite respondents to fill out the questionnaire according to the instructions. The research instrument used was a questionnaire. The data taken is primary data and data analysis using the Chi-Square test. The results showed that there was a relationship between knowledge and the participation of pregnant women in the Covid-19 vaccination program at the South Manokwari District Health Center with a p value α value (0.05). The conclusion is that the knowledge of pregnant women is a factor that can influence the participation of pregnant women to take part in the Covid-19 vaccination program. Keywords: Covid-19 Vaccination, Knowledge, Participation, Pregnant Women  ABSTRAK Ibu hamil lebih rentan terhadap penyakit atau infeksi, pada masa pandemi Covid-19, sangat penting bagi Ibu hamil untuk mengetahui resiko yang dapat terjadi ketika tubuh terinfeksi virus Covid-19 karena ibu hamil lebih cenderung memiliki sistem imunitas tubuh yang rendah. Selain itu, berbagai penelitian juga menyatakan bahwa wanita hamil yang telah melakukan vaksin Covid-19 dapat mengembangkan antibodi yang ada dalam darah tali pusat bayi. Hal ini menunjukkan bahwa bayi dapat menerima manfaat perlindungan dari vaksin, selain manfaat bagi wanita hamil. Tujuan dari penelitian ini adalah untuk menganalisis hubungan pengetahuan dengan keikutsertaan ibu hamil dalam program vaksinasi covid-19 di Puskesmas Wilayah Distrik Manokwari Selatan Kabupaten Manokwari. Jenis penelitian ini merupakan penelitian analitik dengan pendekatan cross-sectional study  yang bertujuan untuk menganalisis hubungan pengetahuan dengan keikutsertaan ibu hamil dalam program vaksinasi Covid-19 dimana variabel independen dan variabel dependen diukur pada waktu yang bersamaan. Peneliti hanya melakukan observasi tanpa melakukan intervensi terhadap subjek penelitian Sampel dalam penelitian ini adalah semua ibu hamil yang berkunjung di Puskesmas Wilayah Distrik Manokwari Selatan dengan teknik total sampling. Penelitian ini menggunakan subjek penelitian manusia yaitu sebanyak 108 responden yang akan diberikan kuisioner. Peneliti meminta kesediaan ibu hamil untuk menjadi responden penelitian. Menjelaskan tentang tujuan dan manfaat penelitian, kemudian menandatangani persetujuan mengikuti penelitian setelah mendapatkan penjelasan. Peneliti memberikan kuisioner kepada responden. Mempersilahkan responden mengisi kuisioner sesuai petunjuk. Instrumen penelitian yang digunakan adalah kuisioner. Data yang diambil merupakan data primer dan analisa data menggunakan uji Chi-Square. Hasil penelitian menunjukan bahwa terdapat hubungan pengetahuan dengan keikutsertaan ibu hamil dalam program vaksinasi covid-19 di di Puskesmas Wilayah Distrik Manokwari Selatan dengan nilai p value nilai α (0,05). Kesimpulan yaitu pengetahuan ibu hamil merupakan faktor yang dapat mempengaruhi keikutsertaan ibu hamil untuk mengikuti program vaksinasi Covid-19. Kata Kunci : Vaksinasi Covid-19, Pengetahuan, Keikutsertaan, Ibu Hamil